Amino modified iodinated BODIPY photosensitizer for highly efficient NIR imaging-guided photodynamic therapy with ultralow dose. (October 2021) - Tian, Youliang; Cheng, Quan; Dang, Huiping; Qian, Hongyun; Teng, Changchang; Xie, Kai; Yan, Lifeng
Abstract: In PDT, high doses of photosensitizers can lead to prolonged patient photosensitivity and undesired side effects. As a classic fluorescent dye, BODIPY has attracted much attention in optical diagnosis and therapy due to its excellent stability, effective singlet oxygen production, and flexible modification. Herein, we synthesized successfully two organic near-infrared BODIPY derivatives with active groups. NO2 -BDPI could be transformed into NH2 -BDPI after responding to hydrogen sulfide in solution and brought an apparent color change. And both dyes possessed excellent single oxygen production capacity ( Φ Δ = 0.629 for NO2 -BDPI and Φ Δ = 0.688 for NH2 -BDPI). After being encapsulated with an amphiphilic polypeptide, NH2 -BDPI could be assembled into nano–NH2 –BDPI particles that own good water solubility and passively tumor-targeting via the enhanced permeability and retention (EPR) effect. Benefiting from the admirable cellular uptake and excellent intracellular ROS generation in vitro, the nano–NH2 –BDPI shows splendid PDT effect towards 4T1 and HeLa cells under very low doses (0.24 μM) and NIR power density (660 nm 10 mW/cm 2 ). In vivo experiment, the nano-photosensitizer exhibited highly effective tumor suppression and ablation under a 40 mW/cm 2 NIR irradiation. The exploration demonstrated the commendable PDT effect of NH2 -BDPI and made it be a potential candidate for further NIR imaging-guided PDT research in clinical application. Highlights: Nitryl and amino-modified iodinated BODIPY photosensitizer (PS) have been synthesized. Both of them show NIR fluorescence and high singlet oxygen quantum yield. Polypeptide based nanoparticles have been prepared to encapsulate the PSs. The nanoparticles show efficient NIR imaging-guided photodynamic therapy for cancer.